Estimation of Serum Creatinine Level of Preeclamptic Patients in Bangladesh - Khatun, Siddika; Sajid, Khandaker Md Tasnim; Rahman, Md Arifur; Jahan, Tarana; Nasir, Salma; Shanta, Morsheda Akhter (Journal of Brahmanbaria Medical College, 2026)
Background: Preeclampsia remains a major contributor to maternal and fetal morbidity and mortality. While its exact cause is not fully understood, changes in serum creatinine levels have been implicated in its development. This study aimed to assess serum creatinine levels in women with preeclampsia to support early diagnosis and prevent complications using accessible biochemical markers. Materials and methods: A cross-sectional study was conducted in the Department of Biochemistry at Mymensingh Medical College, in collaboration with the Department of Obstetrics and Gynecology at Mymensingh Medical College and Hospital. A total of 120 pregnant women were enrolled through purposive (Non-random) sampling based on defined inclusion and exclusion criteria. Among them, 60 women diagnosed with preeclampsia were designated as the case group and 60 normotensive pregnant women served as controls. Serum creatinine levels were measured and reported as mean ± Standard Deviation (SD). The Serum Uric Acid- to-Creatinine (SUA/Scr) ratio was analyzed using logistic regression. Data were analyzed with SPSS version 21 and group comparisons were performed using Student’s unpaired t-test. Results: Serum creatinine levels were significantly higher in preeclamptic patients compared to controls (p < 0.001). Conclusion: Elevated serum creatinine levels in preeclamptic women highlight its potential role as a simple, cost- effective biomarker for early detection and management of preeclampsia. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 25-29